Could Near Infrared Spectroscopy (NIRS) be the new weapon in our fight against Necrotising Enterocolitis? - Howarth, Claire; Banerjee, Jayanta; Leung, Terence; Aladangady, Narendra (Frontiers in Pediatrics, 2022)
There is no ideal single gut tissue or inflammatory biomarker available to help to try and identify Necrotising Enterocolitis (NEC) before its clinical onset. Neonatologists are all too familiar with the devastating consequences of NEC, and despite many advances in neonatal care the mortality and morbidity associated with NEC remains significant. In this article we review Near Infrared Spectroscopy (NIRS) as a method of measuring regional gut tissue oxygenation. We discuss its current and potential future applications, including considering its effectiveness as a possible new weapon in the early identification of NEC.